2018
DOI: 10.1055/s-0038-1667203
|View full text |Cite
|
Sign up to set email alerts
|

The Current Online Face of U.S. Academic Ophthalmology

Abstract: Purpose To evaluate the comprehensiveness and navigation ease of online content from Web sites of U.S. academic ophthalmology departments. Design Cross-sectional analysis of 117 U.S. academic ophthalmology department Web sites from October 1 to October 31, 2017. Methods Data were obtained on various categories, including: clinical access and subspecialty services, social media, patient support and accessibility, residency and fellowship details, and research and faculty characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…3 In 2003, Mayo et al reported 83% of ophthalmology programs had departmental Web sites, 17 but the usage of the Internet has evolved since that time. Begaj et al has examined the comprehensiveness of academic ophthalmology department sites, 18 but we only analyzed factors that may be of concern to prospective trainees in application decision-making. Our goal was to conduct this study from a student-centered approach to identify areas of improvement to assist programs in developing more comprehensive Web sites.…”
Section: Discussionmentioning
confidence: 99%
“…3 In 2003, Mayo et al reported 83% of ophthalmology programs had departmental Web sites, 17 but the usage of the Internet has evolved since that time. Begaj et al has examined the comprehensiveness of academic ophthalmology department sites, 18 but we only analyzed factors that may be of concern to prospective trainees in application decision-making. Our goal was to conduct this study from a student-centered approach to identify areas of improvement to assist programs in developing more comprehensive Web sites.…”
Section: Discussionmentioning
confidence: 99%